Effects of Vancomycin on Platelets, Plasma Proteins and Hepatitis B Surface Antigen - Coller, Barry S; Lundberg, W. B; Gralnick, Harvey R (Thrombosis and Haemostasis, 1975)
The antibiotic vancomycin shares many similarities with ristocetin, an agent noted for its effects on platelets and plasma fibrinogen. Vancomycin did not aggregate platelets as ristocetin, but platelets were incorporated into precipitates induced by vancomycin. Fibrinogen and factor VIII were precipitated from plasma at low concentrations of vancomycin. The precipitated fibrinogen remained clottable. Hepatitis B surface antigen was selectively precipitated from serum and could be recovered from the precipitate. Rabbits receiving bolus intravenous injections of high doses of vancomycin developed hypofibrinogenemia and thrombocytopenia within minutes and often went on to die. Studies with 125I-vancomycin revealed little stable binding of the antibiotic to platelets or fibrinogen. A relationship is suggested between the potent protein precipitating effects and phlebitis at the infusion site commonly associated with vancomycin therapy.